Early Intervention as the Foundation for Early Childhood Math Learning - Onoshakpokaiye E. Odiri; Onyekeshin Ishioma Blessing (Darul Yasin Al Sys, 2026)
This study examines the effects of focused instructional strategies on young children’s conceptual growth in mathematical reasoning and explores how early numeracy abilities influence later mathematical achievement and broader cognitive development. Drawing on empirical research from diverse educational settings, it compares traditional instruction and play-based learning (PBL), both of which are shown to support the development of early arithmetic skills, with particular attention to student engagement, cognitive growth, and numeracy competence. The review analyzes how early mathematical skills, such as number sense, spatial reasoning, and problem-solving—shape academic performance into adolescence and discusses the roles of play-based learning, technology-enhanced approaches, and structured instruction in fostering these foundational concepts. Employing a qualitative approach, the study synthesizes relevant literature on cognitive readiness, early childhood mathematics development, instructional and play-based interventions, and conceptual growth in early mathematics, as well as the longitudinal impact of early childhood mathematics on later academic outcomes. Overall, the findings underscore early intervention as a critical foundation for early childhood mathematics learning and highlight the need for carefully designed pedagogical strategies that integrate play, explicit instruction, and rich learning environments to optimize young children’s mathematical and cognitive development.